THE ROLE OF INTERACTIVE TEACHING METHODS IN DEVELOPING UNIVERSITY STUDENTS’ COMMUNICATIVE COMPETENCE - Gulmira Rakhmonova (TADQIQOTLAR, 2026)
Abstract The development of communicative competence has become one of the primary objectives of modern higher education. In the context of globalization and increasing academic and professional mobility, university graduates are expected to possess not only subject-specific knowledge but also effective communication skills. This study examines the role of interactive teaching methods in developing university students’ communicative competence. The research explores the theoretical foundations of communicative competence and analyzes the effectiveness of interactive methods such as role plays, discussions, debates, case studies, project-based learning, and collaborative tasks. The findings suggest that interactive teaching methods significantly enhance students’ linguistic, sociolinguistic, discourse, and strategic competences by creating authentic communication opportunities and increasing learner engagement.